Assertive Acts in Digital Communication of BTS's Official Instagram Captions - Anak Agung Ari Purnami; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Abstract This study examines assertive actions in digital communication on BTS's Instagram captions, exploring how these linguistic actions shape communication with fans in the dissemination of information. Assertive illocutionary acts are defined as utterances in which the speaker commits to the truth of a proposition, serving to convey facts, provide information, or describe events. This research uses Yule's (1996) and Searle's (1985) theory for a deeper analysis of the function of assertives. This research uses descriptive qualitative methods for data presentation. A total of 114 assertive actions were identified and analysed from 80 Instagram posts. The findings indicate that informing is the most dominant assertive function, with 64 instances (56.14%) identified. Descriptions accounted for 48 instances (42.10%), while 'stating' 2 instances (1.76%). This result highlights that 'Informing' is the main assertive strategy for efficiently conveying important information and updates to the global ARMY or fans of BTS through the official BTS Instagram platform. Keywords: Illocutionary act,assertive,Intagrams caption,BTS Abstrak Studi ini meneliti tindakan asertif dalam komunikasi digital pada keterangan Instagram BTS, mengeksplorasi bagaimana tindakan linguistik ini membentuk komunikasi dengan penggemar dalam penyebaran informasi. Tindakan ilokusi asertif didefinisikan sebagai ungkapan di mana pembicara berkomitmen pada kebenaran sebuah proposisi, yang berfungsi untuk menyampaikan fakta, memberikan informasi, atau menggambarkan peristiwa. Penelitian ini menggunakan teori Yule (1996) dan Searle (1985) untuk analisis yang lebih mendalam tentang fungsi asertif. Penelitian ini menggunakan metode kualitatif deskriptif untuk penyajian data. Sebanyak 114 tindakan asertif diidentifikasi dan dianalisis dari 80 postingan Instagram. Temuan menunjukkan bahwa fungsi asertif yang paling dominan adalah memberi informasi, dengan 64 contoh (56,14%) yang teridentifikasi. Deskripsi menyumbang 48 contoh (42,10%), sementara tipe ‘stating’ ditemukan 2 contoh (1,76%). Hasil ini menyoroti bahwa tipe ‘informing' adalah strategi asertif utama untuk menyampaikan informasi penting dan pembaruan secara efisien kepada penggemar global atau ARMY melalui platform Instagram resmi BTS. Kata kunci: Illocutionary act, assertive, Caption intagrams, BTS